الإستخلاف في ظل الوظيف العمومي على ضوء القانون 06/03 -قطاع التربية نموذجا - ثامر, مبروكة; شايب, اسمهان (University of Eloued جامعة الوادي, 2022)
تختلف نضم الوظيفة العامة في العالم، فكل دولة تنتقي نظام الذي يتماشى وتوجيهاتها السياسية والإقتصادية ووضعتها الإجتماعية . تبنت الج ا زئر بعد استقلالها نظام المغلق للوظيفة العمومية كحتمية ملزمة عليها في وضعها أناذاك، وليس خيار لإعتبا ا رت سياسية على غ ا رر كل منظ وماتها القانونية إلى غاية 900 الذي أبرز نظام التعاقد في كل القطاعات والإدا ا رت العمومية، / صدور الأمر 00 خاصة قطاع التربية الوطنية الذي إعتمد على نظام التعاقد الأساتذة في مكان الأساتذة الدائمين في الحالات التي سمح بها القانون ويعتبر نظام الإستخلاف كأحد صور النظام 60 الذي أبقى على نظام التعاقد أي استخلاف / المفتوح وتواصل العمل به في الأمر 60 الأستاذ الذي تجسد في الحالات التالية عند شغور المناصب المالية بصفة مؤقته أو عند تحرير مناصب مالية أثناء السنة الد ا رسية أو عند وجود مناصب مالية شاغرة، في مكان مناصب مخصصة للموظفين المستخلفين، وفو ا ر توقيع العقد مع مديرية التربية الوطنية 068 ، وفي حالة / يكتسب المستخلف حقوق وواجبات التي يتضمنها المسوم الرئاسي 60 ارتكابه أخطاء مهنية يخضع لنظام التأديبي المنصوص عليه في المادة 06 من نفس المرسوم وقد يصل الأمر في حالة جسامة الخطأ إلى فسخ العقد .The public function is different in the world, each country selects a system that is in line with its political, economic and social status. After its independence, Algeria adopted the closed system of public service as an imperative binding on it in its situation at the time, and not an option for political considerations like all its legal systems until the issuance of Order 66/133, which highlighted the contracting system in all sectors and public administrations, especially the national education sector, which relied on the contracting system Professors are in the place of permanent professors in the cases permitted by law. The succession system isconsidered as one of the forms of the open system. It continues to be applied in Order 06/03, which kept the contract system, that is, the succession of the professor, which was embodied in the following cases when financial positions were temporarily vacant or when financial positions were released. During the school year or when there are vacant financial positions, in the place of positions designated for the successor employees, and immediately upon signing the contract with the Directorate of National Education, the successor acquires the rights and duties contained in Presidential Decree 07/308, and in case he commits professional errors, he is subject to the disciplinary system provided for in Article 60 of The same decree, and in the event of the seriousness of the error, the matter may reach the termination of the contract
مذكرة ماستر